P12 Commissioning for Quality and Innovation (CQUIN) schemes—revisiting urinary tract infection (UTI) management. What worked? What lasted? What next?. (19th January 2023) - Slatter, Mandy; Aprilia, Valentin; Boyd, Rebecca; Chan, Teresa
Abstract: Background: UK CQUIN schemes encourage an improvement focus on a specific area of care. In 2019, CQUIN CCG1a: Improving the management of lower UTI in older people 1 was adopted at the RUH resulting in increased alignment with UK guidance on diagnosis and treatment. 2 Our aim was to investigate whether this improvement was sustained two years later. This would help inform quality improvement interventions prior to adoption of the 2022 CQUIN, CCG2: Appropriate antibiotic prescribing for UTI in adults aged 16+. 3 Objectives: Service evaluation of the UTI pathway including compliance with two of the CQUIN care processes for UTI diagnosis in patients age 65+ presenting to ED (not admitted): (i) diagnosis excludes use of urine dipstick in people aged 65+; and (ii) urine sample sent to microbiology as per UK guidance. 2 Methods: A search of the electronic patient record for key terms (Table 1) identified 6076 ED attendances for patients age 65+ between 1 August and 31 October 2021 of which 40 were identified with a primary diagnosis of UTI not requiring hospital admission. Paramedic, ED and Urgent Treatment Centre notes (paper and electronic) were reviewed in detail and information gathered regarding presence/absence of UTI symptoms aligned to diagnostic guidelines; 2 presence/absence of urine dipstick test; and presence/absence of urine sample for culture and susceptibility testing. Findings were compared with identical trust data for patients (admitted and non-admitted) obtained during the 2019 CQUIN: Q1 April–June; Q2 July–September; Q3 October–December. During this period improvement interventions were implemented. Results: See Table 2. Conclusions: Following intensive staff education improved practice regarding urine dipstick testing and appropriate urine sampling in elderly patients with possible UTI was observed during the 2019 CQUIN period. Two years later this improvement had not been sustained. When planning interventions during the 2022 CQUIN, 3 consideration should be given to a bundle of interventions including education, data feedback and systems improvement, for example, computerized decision support systems (CDSS) to embed sustained change. Table 1. Key terms used to search electronic patient record when identifying eligible patients Search terms Search fields Urin, UTI, pyelonephritis, cystitis, urosepsis, CAUTI, AKI, Acute Kidney Injury, Flank pain Reason for visit, Chief Complaint, Presenting Complaint, ECDS Table 2. Percentage compliance with CQUIN care processes for UTI diagnosis in patients age 65+ Data collection period No. of patients Patients with urine dipstick, % (target 0%) Patients with documented symptoms and urine sample, % (target 100%) Patients with no documented symptoms and urine sample, % (target 0%) Urine sampling decision aligned with UK guideline, 2 % 2019 CQUIN Q1 100 20 89 95 72 2019 CQUIN Q2 100 3 93 79 83 2019 CQUIN Q3 100 6 93 60 90 COVID pandemic ȃPre 2022 CQUIN 40 68 60 47 58